BUXORO AMIRLIGIDA QOZILIK TIZIMINI ISLOH QILISHGA QARATILGAN ISLOHOTLAR(XIX ASR) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
The judicial system of the Bukhara Emirate in the 19th century was developed during the Manghit dynasty and improved through reforms. The qazi system was based on religious-legal principles and played a key role in both central and local administration. Qazis adjudicated civil and criminal cases, ensuring compliance with Sharia law. The qozikalon acted as the supreme judge and oversaw appeals. During Amir Shohmurod’s reign, a supreme judicial body consisting of forty a’lam and a council of muftis was established. Court proceedings required the personal presence of both the plaintiff and the defendant. The reforms reorganized lower courts, controlled qazi activities, and ensured fair judicial processes. The system became multi-tiered, Sharia-based, transparent, and equitable.